2011
DOI: 10.1007/s11095-011-0375-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and In Vitro-In Vivo Evaluation of Polymeric Implants for Continuous Systemic Delivery of Curcumin

Abstract: Our data showed that these implants were able to release curcumin for long duration and to modulate liver phase I and phase II enzymes, demonstrating curcumin's biological efficacy delivered via this delivery system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 40 publications
3
56
1
Order By: Relevance
“…A good correlation of in vitro studies and results gained from computer modeling of pharmacokinetic data to in vivo experiments was shown for protein-loaded tristearin implants [18]. Other studies revealed a faster release of incorporated substances from implantable system in vivo than in vitro [19][20]. The present study aimed at comparing the release from HES-P(EG) 6 MA and HES-MA hydrogel disks and microparticles in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 72%
“…A good correlation of in vitro studies and results gained from computer modeling of pharmacokinetic data to in vivo experiments was shown for protein-loaded tristearin implants [18]. Other studies revealed a faster release of incorporated substances from implantable system in vivo than in vitro [19][20]. The present study aimed at comparing the release from HES-P(EG) 6 MA and HES-MA hydrogel disks and microparticles in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 72%
“…23 Therefore, curcumin remains to be a pharmaceutical challenge with regard to its solubility limitations. Several novel delivery systems were proposed in recent years as means to improve its bioavailability, including polymeric implantable delivery systems, 23 rubusoside-solubilized curcumin formulation, 24 nanoparticle-encapsulating curcumin prepared by the emulsion technique, 25 injectable curcuminloaded poly(ethylene oxide)-b-poly(g-caprolactone) micelles for controlled delivery of curcumin 26 among others. Very promising delivery system appears to be "nanocurcumin," polymeric nanoparticleencapsulated curcumin, readily dispersed in aqueous media and with confirmed anticancer potentials in preclinical in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…Till now a number of curcumin delivery strategies have been developed such as micelles (Ma et al, 2008), liposomal vesicles (Nguyen et al, 2016), nanoparticles (Bisht et al, 2007;Shaikh et al, 2009;Anand et al, 2010), nanoemulsions (Ganta and Amiji, 2009), phospholipid complexes (Maiti et al, 2007) and polymeric implants (Bansal et al, 2011) etc. to enhance its bioavailability.…”
Section: * Corresponding Authormentioning
confidence: 99%